Organotin Compound Derived from 3-Hydroxy-2-formylpyridine Semicarbazone: Synthesis, Crystal Structure, and Antiproliferative Activity - Joanna Wiecek; Dimitra Kovala-Demertzi; Zbigniew Ciunik; Joanna Wietrzyk; Maria Zervou; Mavroudis A. Demertzis (Bioinorganic Chemistry and Applications)
The novel diphenyltin(IV) compound [Ph2(HyFoSc)Sn] (2), where H2HyFoSc (1) is 3-hydroxy-2-formylpyridine semicarbazone, was prepared and characterized by vibrational and NMR (1H, 13C) spectroscopy. The structure of [Ph2(HyFoSc)Sn] was confirmed by single-crystal X-ray crystallography. The doubly deprotonated ligand is coordinated to the tin atom through the enolic-oxygen, the azomethine-nitrogen, and phenolic-oxygen, and so acts as an anionic tridentate ligand with the ONO donors. Two carbon atoms complete the fivefold coordination at the tin(IV) center. Intermolecular hydrogen bonding, C-H→𝜋, and 𝜋→𝜋 interactions combine to stabilize the crystal structure. Compounds 1 and 2 have been evaluated for antiproliferative activity in vitro against the cells of three human tumor cell lines: MCF-7 (human breast cancer cell line), T24 (bladder cancer cell line), A549 (nonsmall cell lung carcinoma), and a mouse fibroblast L-929 cancer cell line.